Pengaruh Literasi Keuangan, Perencanaan Keuangan, dan Lingkungan Sosial Terhadap Perilaku Keuangan Pegawai Pemerintah Non Pegawai Negeri (PPNPN) Universitas Pendidikan Ganesha - Wijayanti, Ema; Kadek Sinarwati , Ni; Indah Rahmawati , Putu (IPB University, 2024)
The purpose of this study is to examine the partial and simultaneous effects of financial literacy, financial planning, and social environment on PPNPN Undiksha's financial behaviour. Utilising a questionnaire as a research instrument, quantitative research is the method employed. The sampling technique used was purposive sampling with a total sample of 56 people consisting of educational staff (PPNPN) with Contract Agreements and assigned to the finance section of the Rectorate, institutions and various faculties within Undiksha. It is known that Undiksha includes 9 faculties including Postgraduate. The findings demonstrated that financial behaviour is significantly and favourably impacted by financial literacy, financial planning, and the social environment. Additionally, financial behaviour is significantly and favourably impacted by financial literacy, financial planning, and the social environment combined. on the PPNPN Undiksha's financial conduct. These findings have implications and contribute to PPNPN Undiksha to increase financial literacy, finalize financial planning and choose a positive social environment to be able to foster good financial behavior in each individual.